2016
DOI: 10.1002/srin.201600234
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Behavior and Microstructural Evolution of Vanadium-Added TRIP-Assisted Annealed Martensitic Steel

Abstract: (1 of 4) 1770053 Cover Photo: Electrochemical reactions always occur at the electrode-slag and slag-metal melt interfaces during the electroslag remelting (ESR) process. The cover shows a schematic representation of this process. A numerical model is developed to investigate those reactions together with the ion transport phenomenon. The cover fi gure is supplied by Christian Doppler Laboratory for Advanced Process An overview and discussion on a range of electromagnetic effects, including magnetic damping, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Precipitation strengthening is influenced by many factors, [21,220,221] including: size, structure, composition and chemical ordering of precipitates; interface coherency and orientation relationship of precipitate and matrix; number density, inter-particle spacing and particle size distribution. Based on whether a dislocation can pass through the precipitate or has to loop around a precipitate, the strengthening mechanism is usually divided into two types: shearing and Orowan looping.…”
Section: Understanding Of Precipitation Strengthening By In Situ Analysis Of Precipitate-dislocation Interactionsmentioning
confidence: 99%
“…Precipitation strengthening is influenced by many factors, [21,220,221] including: size, structure, composition and chemical ordering of precipitates; interface coherency and orientation relationship of precipitate and matrix; number density, inter-particle spacing and particle size distribution. Based on whether a dislocation can pass through the precipitate or has to loop around a precipitate, the strengthening mechanism is usually divided into two types: shearing and Orowan looping.…”
Section: Understanding Of Precipitation Strengthening By In Situ Analysis Of Precipitate-dislocation Interactionsmentioning
confidence: 99%
“…During manufacturing, the final heat treatment is quench-hardening to form the supersaturated martensite, followed by an ageing treatment at about 450-525°C to stimulate precipitation from the supersaturated matrix [6][7][8]. These alloys can make use of multiple alloying elements for the precipitation [9][10][11][12][13][14][15], Cu being one of the most common elements. Cu has high solubility in the austenite and low solubility in the martensite, and its high supersaturation in the martensite enables the formation of a significant amount of very fine precipitates early during ageing [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The VC nano-precipitates were found to produce an effective precipitation hardening effect. Li et al [12] studied the precipitation behavior and microstructural evolution of vanadium-added martensitic steel, and also found that the precipitation strengthening contribution of the nano-sized VC particles was 167 MPa by the Ashby-Orowan mechanism.…”
Section: Introductionmentioning
confidence: 99%